The media in Europe's small nations - Jones, Huw David (Newcastle upon Tyne : Cambridge Scholars Publishing, 2014)
Small nations are growing in prominence. In 1950, there were 22 sovereign European states with a population below 18 million. Today there are 36 - not to mention many more stateless nations. What are the particular characteristics of the media in small nations? What challenges do broadcasters and other media institutions in these countries face, how can these be overcome, and are there advantages to operating in a small national context? How are small nations represented on screen, and how do ...
"It comes out of an international conference on the media and culture in small nations organised in summer 2011 at the University of Glamorgan ... by the Centre for the Study of Media and Culture in Small Nations on behalf of the Welsh Media Association Cyfrwng"--Introduction.
Includes bibliographical references.
Print version record.
Added to collection customer.56279.3
Keywords: Mass media -- Europe; States, Small; PSYCHOLOGY -- Social Psychology; Mass media; States, Small; Europe; Autonome Region; Kleinstaat; Massenmedien; Europa; Fallstudiensammlung; Electronic books